Analisis Sistem Pengendalian Internal Terhadap Penjualan Kredit Pada PT. Astra International Tbk-Isuzu Cabang Medan - M. Fahrurozi Nasution; Hendra Harmain; Atika Atika (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Sales on credit will certainly lead to very large receivables for the company, so the company really needs good management so that it can avoid all forms of irregularities, fraud, and fraud. A good accounting information system implemented by the company also greatly influences the management function in implementing internal control. This research was conducted with the aim of knowing the effectiveness of the internal control system on credit sales implemented at PT. Astra International Tbk – Isuzu Medan Branch and its compliance with COSO criteria. This research is a qualitative research. The data used are primary and secondary data. Primary data comes from direct interviews and secondary data in the form of organizational structure and job descriptions as well as forms used in credit sales. The data analysis technique used in this research is descriptive qualitative by comparing the theories with the implementation of the internal control system at PT. Astra International Tbk – Isuzu Medan Branch. The results of this study found that the implementation of the internal control system at PT. Astra International Tbk - Isuzu Medan Branch has been running quite effectively, although there are still a few deficiencies that have caused the performance of the unit administration staff to not be optimal in credit sales transactions. Implementation of the internal control system at PT. Astra International Tbk – Isuzu Medan Branch also complies with COSO criteria.